Pro-inflammatory cytokines in Turkish children with protein-energy malnutrition - Haluk Dülger; Mehmet Arik; M. Ramazan Şekeroğlu; Mehmet Tarakçioğlu; Tevfik Noyan; Yaşar Cesur; Ragip Balahoroğlu (Hindawi Limited, 2002)
Background: Protein-energy malnutrition (PEM) results from food insufficiency as well as from poor social and economic conditions. Development of PEM is due to insufficient nutrition. Children with PEM lose their resistance to infections because of a disordered immune system. It has been reported that the changes occurring in mediators referred to as cytokines in the immune system may be indicators of the disorders associated with PEM.